Advancing considerations of context in the evaluation and implementation of evidence-based biomedical HIV prevention interventions: a review of recent research. Issue 1 (7th January 2023) - Velloza, Jennifer; Roche, Stephanie; Concepcion, Tessa; Ortblad, Katrina F.
Abstract : Purpose of review: A paradigm shift is needed in how we think about biomedical HIV prevention product effectiveness. Often, we expect randomized trial findings to be generalizable across populations and settings where products will be delivered, without consideration of key contextual drivers that could impact effectiveness. Moreover, researchers and policy-makers generally discount products with varied effect sizes across contexts, rather than explicating the drivers of these differences and using them to inform equitable product choice and delivery. We conducted a review of the recent HIV prevention research to advance considerations of context in choices of when, why, and how to implement biomedical HIV prevention products, with a particular focus on daily oral preexposure prophylaxis (PrEP) and the dapivirine vaginal ring (DPV). Recent findings: Findings across recent studies of PrEP and DPV emphasize that products that do not work well in one context might be highly desirable in another. Key contextual drivers of PrEP and DPV effectiveness, use, and implementation include population, health system, cultural, and historical factors. We recommend conceptualization, measurement, and analysis approaches to fully understand the potential impact of context on prevention product delivery. Execution of these approaches has real-world implications for HIV prevention product choice and could prevent the field from dismissing biomedical HIV prevention products based on trial findings alone. Summary: Ending the HIV epidemic will require tailored, person-centered, and equitable approaches to design, implement, and evaluate HIV prevention products which necessitates considerations of context in ongoing research and implementation.